Comparıson Of Bond Strength New And Recycled Brackets To Shear And Tensıle Forces - Gökhan Önçağ; Yahya Şerif Tosun; Ali Vehbi Tuncer (Galenos Yayinevi, 2001)
In this study bond strength of new and recycled brackets with Esmadent technique and by burning the adhesives with 450-500° C copper resistance wire technique, to shear and tensile forces has been compared. 60 first premolars extracted for orthodontic reasons with no caries have been divided in to 3 groups of 20. The teeth in the first group were bonded with new brackets while the teeth in the second group were bonded with recycled brackets by Esmadent technique and the 20 teeth in the third group were bonded with recycled brackets in the clinic and using the same type of adhesive (Ortho organizer Advantage No-mix Direct Bonding). Forestadent standart edgewise brackets were used in this study. 10 of the brackets were subjected to tensile test while the other 10 in each group were subjected to the shear test using the Universal Testing Apparatus with 0,5 mm/min. constant force. The results were evaluated with variance statistical analysis. The importance tests between the means were evaluated with the Neumann Keuls analysis. The results of the tensile test intergroup were found to be statistically significant (YAK-YENİ p<0,01/REC-YAK p<0,05/REC-YENI p<0,05). The lowest mean in this test was found in the YAK group (the group that was recycled in the clinic by burning the adhesive over 450-500°C copper wire), while the highest level was found in the YENİ (new brackets) group. In the group of the shear test the highest bonding rate was seen in the YENİ group, and the results between the REC (recycled brackets using the Esmadent technique) and YAK group were found to be very close to each other. While the results between YENİ and the other groups were statistically significant, there was no statistically significant difference between REC and YAK groups. The result of shearing test intragroup were found statistically significant (YENİ P<0,01-REC p<0,05).